PENGARUH AIRLINE QUALITY TERHADAP CUSTOMER SATISFACTION MASKAPAI PENERBANGAN CITILINK DI BANDARA JUANDA SURABAYA - Rida Yusfriska; Indarini; Dudi Anandya (Perpustakaan Universitas Surabaya, 2021)
Abstract — This study aims to prove the influence of Airline Quality (airline tangible, terminal tangible, personnel services, empathy, and airline image) to customer satisfaction on Citilink Airlines at Juanda Airport in Surabaya. This type of research is basic research that is included in the type of casual research. Respondents in this study amounted to 150 people. The Analysis in this research using a model of SEM (Structural Equation Modeling) and processed by SPSS Software 25.0 for windows and AMOS 22.0 for Windows for testing model of Measurement and Structural. The results of this research indicate that the five hypotheses were supported and positive significantly influenced customer satisfaction. Keywords: Airline Quality, Customer Satisfaction, Airline Industry, Service Quality Abstrak— Penelitian ini bertujuan untuk membuktikan pengaruh dimensi Airline Quality (airline tangible, terminal tangible, personnel services, empathy, dan airline image) terhadap customer satisfaction Penumpang Maskapai Penerbangan Citilink di Bandara Juanda Surabaya. Jenis penelitian yang digunakan adalah jenis penelitian basic research yang termasuk dalam tipe penelitian kausal. Responden dalam penelitian ini berjumlah 150 orang. Analisis dalam penelitian ini menggunakan SEM (Structural Equation Modeling) dan diolah menggunakan software SPSS versi 25.0 for windows serta AMOS versi 22.0 for Windows. pada penelitian ini menunjukan bahwa kelima hipotesis terdukung dan berpengaruh positif secara signifikan terhadap customer satisfaction. Kata kunci: Airline Quality, Customer Satisfaction, Airline Industry, Service Quality